Serum Adipokine Levels and their Relationship with Fatty Acids in Patients with Chronic Periodontitis - Sete,Manuela Rubim Camara (2015)
Adipokines are present in inflammatory processes and may be directly related to periodontal disease. Moreover, their activities may be regulated by fatty acids. The goal of this study was to quantify the concentrations of the main adipokines, leptin, adiponectin and resistin, and the docosahexaenoic (DHA), docosapentaenoic (DPA), eicosapentaenoic (EPA) and arachidonic (AA) fatty acids, in patients with generalized chronic periodontitis. As a secondary objective, the ratios of these substances in the blood of these patients were evaluated. The study included 15 systemically healthy patients with generalized chronic periodontitis (test group) and 15 patients with gingivitis (control group). Medical and periodontal parameters and blood samples were collected. Serum concentrations of fatty acids were analyzed by gas chromatography and adipokines by multiplex bead immunoassay. There was no significant difference in adipokines between groups. However, there was a tendency for lower values of adiponectin in periodontitis patients. Regarding the fatty acids, they were significantly higher in the test group compared with controls. The res/DHA, res/AA, adipon/DHA, adipon/AA and adipon/DPA ratios were significantly lower in the test group. There was no significant correlation between adipokines and clinical parameters and between adipokines and fatty acids levels. It was concluded that generalized chronic periodontitis patients showed significantly higher levels of fatty acids in comparison to gingivitis; adiponectin revealed a trend to lower values in the periodontitis group, even after Ancova correction. The ratios suggest a minor proportion of adiponectin and resistin in relation to the fatty acids in patients with generalized chronic periodontitis.